Introduction to positive economics - Lipsey, Richard G. (London, 1983)
This is an introductory textbook in economics, starting at an elementary stage and progressing, in some places, to an intermediate level. It is designed to be read as a first book in economics. I hope, on the other hand, that the book will not be without interest for someone who has already studied one of the many existing basic textbooks written at a first-year university standard. The details of the complete revision which this latest edition has received are given in the 'Notes on the Sixth Edition' which follow this preface.. The book had its beginnings when I was asked to give the basic economic theory lectures for revised B.Sc.(Econ.) degree introduced at the London School of Economics in October 1961. Istarted to write my first few lectures and, almost before I knew it, a book was well under way. Had I appreciated at the outset what was involved in carrying such a project through to completion, Iwould never have begun it, but that is probably true of a great many enterprises in all fields. There are three major themes of this textbook which should be mentioned here: first, an attempt to explain what economic theory is about and how one can go about criticizing it effectively and hence improving it; second, an attempt to elaborate, in so far as is possible within the confines of an introduction to economic theory, the relation between theory and real-world observations; and third, a consideration of the relation between economic theory and economic policy. The first major theme of this book is how one can go about being intelligently and constructively critical of the existing body of economic theory. I have tried to address myself throughout to the intelligent student of honours-school quality. I have assumed that the student was interested in the subject and that he or she wished to know, at every stage, what was going on and why. There is a tradition of trying to sneak quite complex bits of analysis past students without telling them what is happening. This may be the best thing to do if the object is to get through an examination a large mass of people who have neither interest nor ability in economics, and who are hostile to the basic idea of a Social Science. I am not interested in reaching such a public. I have assumed that I am addressing an intelligent set of students, who may or may not be honours students and intending specialists, but who want to learn and who do not have closed minds. One of the troubles with the traditional approach of sneaking analysis past the student is that, when the intelligent reader feels that there is something wrong with what has been taught, he or she does not know how to go about being critical of it in an effective way. I have made a point of telling the student what is going on, to say 'now we are doing comparative-static equilibrium analysis' or whatever it might be, and I have devoted considerable space to an analysis of both sensible and silly criticisms of the theories described. I do not accept the idea that the possibility of criticizing what has been learned should n be mentioned because, if it is, the student will be led to make hasty and confused criticisms. A go student will always attempt criticisms and evaluations of what he or she has been taught. It seen me that criticisms are much more likely to be informed and relevant ones if students are given practice and instruction in how to set about effectively challenging what they have been taugh if they meet a conspiracy of silence on this topic.
Keywords: Economics